(3ebOeI aj GdeYGOdGJ GdJaGVdjIs - (3QTOj(B, (3Ndjds ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2008)
(3CSGSjGJ GdLHQ GdNWj, GdeYGOdGJ GdJaGVdjI GdYGOjI ef GdeQJHI GdChdi h GdeYGOdGJ GdJaGVdjI GdNWjI, GdeYGOdGJ GdNWjI ef GdeQJHI GdKGfjI PGJ GdYdGbI GdKGHJI , GdeYGOdGJ GdNWjI ef GdeQGJH GdYdjG , JMhjd dGHdGS, GdMd HGdeJSdSdGJ, efXheI eYGOdGJ JaGVdjI NWjI h CNjQG JWHjbGJ ddeYGOdGJ eY GdCLhHIs
Keywords: (3GdLHQ GdNWjs; (3GdQjGVjGJs; (3GdeYGOdGJ GdJaGVdjIs